PROBLEMATIKA DAN TANTANGAN PESEK (Pembelajaran Sejarah Emotif dan Kontroversial) - Widiadi, Aditya (Jurnal Sejarah dan Budaya, 2009)
Abstract: Controversy is always being part of history, and even the relationship between history and controversy always canât be separated. Controversy in history actually can indicate as health climate of academic. Eventhough controversial history triggering emotive situation between historians and their supporters, history is more interesting when it has different versions. The problem is on how to manage the emotive and controversial history in learning situation at school. Teaching emotive and controversial history can be separated into dichotomy aspects, in one side it gives problems in learning situation, but in the other hand it give challenges for teacher to sustain interesting and enjoyble of history learning.